PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN MENGGUNAKAN JASA â€œRUMAH LAUNDRYâ€ DI KECAMATAN PALU SELATAN - NINGSIH, VERA (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2015)
The purpose of this study is to determine the influence of quality of service that consists of physical evidence (X1), empathy (X2), reliability (X3), responsiveness (X4) and assurance (X5) on consumer satisfaction using services "Home Laundry" in South Palu Sub-district, both simultaneously and partially. The type of study is causal-descriptive. The population consists of all consumers who use the services of "Home Laundry" in South Palu Sub-district. Sampling technique is purposive sampling with a sample size of 60 people. The analytical tool is multiple linear regressions analysis. Based on the results of multiple linear regression analysis show that the quality of service consists of physical evidence (X1), empathy (X2), reliability (X3), responsiveness (X4) and assurance (X5) simultaneously have significant influence on consumers? satisfaction in using the services of "Home Laundry" in South Palu, with significant values of 0.000> 0.05. Partial test finds that the quality of service consists of physical evidence (X1) = 0.011, empathy (X2) = 0.001, reliability (X3) = 0.001, responsiveness (X4) = 0.000 and assurance (X5) = 0.010 significantly have partial influence on customer satisfaction in using the services of "Home Laundry" in South Palu Sub-district.